ANALYSIS OF CULTURAL DIVERSITY AND SPATIAL ACCESSIBILITY OF CULTURAL FACILITIES IN THE MEDEU AND ALMALY DISTRICTS OF ALMATY - Aizhan Timurovna Akhmedova; Iman Dana Kanyshkyzy (Reviews of Modern Science, 2024)
This article examines the cultural diversity and spatial accessibility of cultural facilities in the Medeu and Almaly districts of Almaty. The aim of the study is to assess the number, types, and distribution of cultural facilities, as well as their accessibility for residents of these districts. The study is based on data about theaters, museums, libraries, and other institutions, as well as methods of spatial analysis. The results identified key issues in ensuring equal access to cultural resources.